Pregnancy Outcome in Cartilage-Hair Hypoplasia, a Rare Form of Dwarfism - Harshithaa Thavarajah; Anne Berndl (Case Reports in Obstetrics and Gynecology)
Background. This case report discusses the pregnancy outcome of a patient with cartilage-hair hypoplasia, a rare form of dwarfism, and multiple previous orthopedic surgeries. Literature on pregnancy outcomes in patients with cartilage-hair hypoplasia is limited. Case. A 32-year-old patient with cartilage-hair hypoplasia presented at 12 weeks’ gestation to the high-risk obstetrics clinic for care. Preterm labor resulted in cesarean delivery at 34 weeks’ gestation with general anesthetic. Breastfeeding was stopped at 6 weeks due to neonatal complications. Conclusion. Pregnancy and delivery were uncomplicated. A multidisciplinary approach allowed for effective management during pregnancy and postnatal care. This is the first known documented case of prenatal care, delivery, and breastfeeding in a woman with this rare disorder.